The relationship between dlPFC activity during unpredictable threat and CO2-induced panic symptoms. Issue 12 (December 2017) - Balderston, Nicholas; Liu, Jeffrey; Roberson-Nay, Roxann; Ernst, Monique; Grillon, Christian
Abstract Panic disorder is characterized by sudden, repeated, and unexpected attacks of intense fear and overwhelming anxiety about when another attack may strike. Patients with panic disorder and healthy individuals with a history of panic attacks show a hypersensitivity to unpredictable threats, suggesting a possible link between panic and sustained anxiety. The purpose of this study was to determine the degree to which induced symptoms of panic relate to fear and anxiety, as well as activity in the neural systems that mediate and regulate these affective states. Psychological and physiological symptoms of panic were assessed during an 8-min 7.5% CO2 challenge task. Psychological, physiological, and neural symptoms of fear and anxiety were measured during two sessions (one psychophysiology and one functional magnetic resonance imaging where subjects experienced several blocks of no threat (N), predictable shock (P), and unpredictable shock (U; NPU threat task). We used a principle component analysis to characterize panic susceptibility (PS), and found that PS significantly predicted dorsolateral prefrontal cortex (dlPFC) activity to the unpredictable cue during the NPU threat task. When examining the weighted beta coefficients from this analysis, we observed that self-reported fear/anxiety during the CO2 challenge negatively loaded onto dlPFC activity during the NPU task. Consistent with this observation, dlPFC activity during the unpredictable cue was also negatively correlated with anxiety during the NPU sessions. Together, these results suggest that panic symptoms and anxiety are regulated by the same prefrontal cognitive control system.